Benson's Microbiological Applications : Laboratory Manual in General Microbiology - Brown, Alfred E (New York : McGraw-Hill, 2012)
Benson's Microbiological Applications has been the gold standard of microbiology laboratory manuals for over 30 years. The 77 self-contained, clearly-illustrated exercises, and four-color format makes Microbiological Applications: Laboratory Manual in General Microbiology, the ideal lab manual. Appropriate for either a majors or non-majors lab course, this lab manual assumes no prior organic chemistry course has been taken.
Includes Appendix A:1-21p.; Reading references R-1p.; Index I:1-6p.
Keywords: Microbiology laboratory manual; Microorganisms; Microbiology